DNA-PKcs is required for cGAS/STING-dependent viral DNA sensing in human cells - Dayana B. Hristova; Marisa Oliveira; Emma Wagner; Alan Melcher; Kevin J. Harrington; Alexandre Belot; Brian J. Ferguson (iScience, 2024)
Summary: To mount an efficient interferon response to virus infection, intracellular pattern recognition receptors (PRRs) sense viral nucleic acids and activate anti-viral gene transcription. The mechanisms by which intracellular DNA and DNA viruses are sensed are relevant not only to anti-viral innate immunity, but also to autoinflammation and anti-tumour immunity through the initiation of sterile inflammation by self-DNA recognition. The PRRs that directly sense and respond to viral or damaged self-DNA function by signaling to activate interferon regulatory factor (IRF)-dependent type one interferon (IFN-I) transcription. We and others have previously defined DNA-dependent protein kinase (DNA-PK) as an essential component of the DNA-dependent anti-viral innate immune system. Here, we show that DNA-PK is essential for cyclic GMP-AMP synthase (cGAS)- and stimulator of interferon genes (STING)-dependent IFN-I responses in human cells during stimulation with exogenous DNA and infection with DNA viruses.